Analysis on product graphs along with the utilisation of restrained step triple connected domination parameter. (27th August 2022) - Mahadevan, G.; Suganthi, M. Vimala; Basira, A. Iravithul
Recently, authors introduced the concept of restrained step tripe connected domination number. In this paper we analysis general results for the strong product of paths and cycles along with application of restrained step triple connected domination number of a graph with reality.